A Simple, Economical and Rapid Method to Isolate High Quality DNA from Oomycetes - Archana, PV; Jeeva, Muthulakshmi Lajapathy; V, Pravi (JOURNAL OF ROOT CROPS, 2015)
Several approaches have been advocated to diagnose and control the devastating diseases caused by the oomycetes, most of which are done using molecular techniques that require DNA with high quantity and quality. An attempt has been made to develop simple, economical and rapid method to isolate high quality DNA from 10 different oomycetes at Central Tuber Crops Research Institute, Thiruvananthapuram, India. This protocol was based on the sodium dodecyl sulphate (SDS) method, which produced high quality DNA, either from liquid or plate cultures, without maceration in liquid nitrogen, devoid of harmful chemicals like Î².mercaptoethanol, phenol, chloroform, etc., and does not require any incubation steps. The total time to complete the whole procedure was less than 30 minutes. The high quantity and purity of the isolated genomic DNA was confirmed by restriction digestion analysis which demonstrated that the developed method provided DNA of sufficient quality for molecular analysis. The method developed is safe, convenient, economical and time saving like commercial DNA extraction kits. It is useful for laboratories with minimum financial resources for handling large number of samples .